Static and dynamic brain morphological changes in isolated REM sleep behavior disorder compared to normal aging - Park, Gilsoon; Jo, Hyunjin; Chai, Yaqiong; Park, Hea Ree; Lee, Hanul; Joo, Eun Yeon; Kim, Hosung (Frontiers in Neuroscience, 2024)
To assess whether cerebral structural alterations in isolated rapid eye movement sleep behavior disorder (iRBD) are progressive and differ from those of normal aging and whether they are related to clinical symptoms.In a longitudinal study of 18 patients with iRBD (age, 66.1±5.7 years; 13 males; follow-up, 1.6±0.6 years) and 24 age-matched healthy controls (age, 67.0±4.9 years; 12 males; follow-up, 2.0±0.9 years), all participants underwent multiple extensive clinical examinations, neuropsychological tests, and magnetic resonance imaging at baseline and follow-up. Surfacebased cortical reconstruction and automated subcortical structural segmentation were performed on T1-weighted images. We used mixed-effects models to examine the differences between the groups and the differences in anatomical changes over time.None of the patients with iRBD demonstrated phenoconversion during the follow-up. Patients with iRBD had thinner cortices in the frontal, occipital, and temporal regions, and more caudate atrophy, compared to that in controls. In similar regions, group-by-age interaction analysis revealed that patients with iRBD demonstrated significantly slower decreases in cortical thickness and caudate volume with aging than that observed in controls. Patients with iRBD had lower scores on the Korean version of the Mini-Mental Status Examination (p=0.037) and frontal and executive functions (p=0.049) at baseline than those in controls; however, no significant group-by-age interaction was identified.Patients with iRBD show brain atrophy in the regions that are overlapped with the areas that have been documented to be affected in early stages of Parkinson's disease. Such atrophy in iRBD may not be progressive but may be slower than that in normal aging. Cognitive impairment in iRBD is not progressive.